Cross layer trigger-based handover scheme for mobile WiMAX networks. (2015) - Pahal, Sudesh; Singh, Brahmjit; Arora, Ashok
Wireless interoperability for microwave access (WiMAX) networks have recently emerged to be a cost-effective solution to provide broadband access over a large coverage area. To maintain service continuity and guarantee the QoS in real-time applications for mobile users, handover delay is one of the main challenges. In this paper, cross layer trigger-based handover scheme is proposed which will be able to offer uninterrupted services to mobile users. The basic idea behind this scheme is to achieve a global optimality by utilising the advantages of cross layer interactions between link layer and network layer. The cross layer triggers generated at lower layers, intimate higher layers about an imminent handover and allow execution of handover processes in layer 2 and layer 3 simultaneously. The analytical and simulation results show that the proposed mechanism enhances the handover performance in terms of handover delay and latency, which, in turn, reduces signalling overload and service disruption significantly.